The e!ects of grit-blasting on surface properties for adhesion - Harris, A.F.; Beevers, A.
A detailed study of the e!ects of grit blasting with di!erent alumina grits on the surface characteristics of mild steel and aluminium alloy substrates is reported. Non-contacting 3D-laser pro"lometry was used to characterise surface texture, and surface energy was measured by static contact angle techniques. The chemical composition of the surface was determined by XPS analysis. Adhesion characteristics were investigated by the measurement of strength of lap shear and tensile butt joints using a two-part room temperature curing epoxy adhesive. As initial joint strengths were relatively insensitive to the changes in grit-blasting parameters, further studies were based on joint response to accelerated ageing conditions. The results indicate that the changes in joint properties associated with roughened surfaces cannot be explained simply by the increased roughness characteristics, such as mechanical keying and increased e!ective bond area. It is evident that changes in physical and chemical properties of the surface, arising from the grit-blasting process contributed signi"cantly to the joint behaviour.
Keywords: SURFACE TREATMENT; SURFACE ROUGHNESS/MORPHOLOGY; CONTACT ANGLES; DURABILITY